2019
DOI: 10.4235/agmr.19.0006
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy Tube Removal for Patients With Advanced Dementia: Case Series Study

Abstract: Background Although the notion of percutaneous endoscopic gastrostomy (PEG) tube placement for patients with dementia has been changing, the number of cases of PEG placement remains high as Japan has become a super-aged society. However, there is insufficient research about the clinical course of dementia patients with PEG, especially regarding PEG extubation after regaining full oral intake. This case series aimed to reveal the demographic data of patients who successfully underwent PEG extubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…“What matters” (i.e., one of the four cornerstones of the age-friendly health system framework) 11 ) is also affected by the social characteristics of populations. While research diversity in aging is considered a pressing issue in the United States, 12 ) knowledge gaps among different societies have been less addressed globally.…”
Section: International and Regional Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…“What matters” (i.e., one of the four cornerstones of the age-friendly health system framework) 11 ) is also affected by the social characteristics of populations. While research diversity in aging is considered a pressing issue in the United States, 12 ) knowledge gaps among different societies have been less addressed globally.…”
Section: International and Regional Perspectivesmentioning
confidence: 99%
“…For instance, providing nutritional support through enteral access has been considered a default in many Asian societies, even in patients with advanced dementia, even though tube feeding in these patients is clinically controversial. 12 , 13 ) Similarly, a recent study suggested that socio-cultural factors pose barriers in initiating discussions about advance care planning in older persons with dementia. 14 ) Specifically, in Chinese culture, discussing matters related to death has been considered taboo.…”
Section: International and Regional Perspectivesmentioning
confidence: 99%
“…To bolster the development of research ideas for older populations in our region, our journal is eager to receive research on population-or region-specific issues, with varying levels of evidence, including qualitative research such as narrative studies, small-scale case series, or proof-of-concept pilot studies. For example, a study from Japan by Hattori et al 5) describing cases of successful removal of percutaneous endoscopic gastrostomy tubes in patients with advanced dementia reflects unique cultural characteristics in East Asian countries regarding the importance of providing oral or enteral nutrition even to terminally frail patients. Similarly, a study from Brunei by Akbar et al 6) reports the perspectives of healthcare providers, including the cultural characteristics of Asian countries in terms of hierarchies among professionals and mood or pain status in less-expressive patients.…”
mentioning
confidence: 99%